Pengaruh Kebisingan Terhadap Kelelahan dalam Pekerjaan Pembangunan SUTT 150 kV Raha Bau-Bau Section 1 - Wiraantaka, Jaka Adiprasetya; Ilham, Ilham; Sumarlin, Sumarlin (Universitas Muhammadiyah Kendari, 2023)
The construction of transmission line is one of the national strategic projects to even out development, especially with regard to the need for electric power. The construction of transmission line Raha – Baubau will connect two islands in Southeast Sulawesi Province, namely Muna Island and Buton Island. PT PLN (Persero) UPP Sulawesi Tenggara as the project director on this project is very concerned about K3 (Occupational Safety and Health) starting from the planning, work, testing and operation stages. Measurements of the work environment have been routinely carried out every semester but there has never been a study on the impact of noise on worker fatigue in the field. The sources of noise during this construction work include breakers, concrete mixers, ironworks, erection towers and stringing machines. With a total workforce of ±80 people and work intensity/noise exposure of 8 hours/day and the impact of noise risks that are not yet known, it is necessary to conduct research to identify and mitigate the risks of fatigue due to noise in the construction work of transmission line Raha-Baubau Section 1.